A ética da compaixão em Schopenhauer: uma moralidade possível. - Santos, Evson Ferreira dos (2023)
In this dissertation, we will work with the title The Ethics Of Compassion In Schopenhauer: A Possible Morality. This research aims to elucidate the author's main ideas, however, specifically about the phenomenon of compassion as practical ethics proposed by the thinker. We will point out below that our compassionate deficiency will compromise the coexistence in the ethos. The being that recognizes itself in the other, including in suffering, is the result of Schopenhauerian morality; it is important to emphasize that this relationship of responsibility is not only between human beings, but between the entire cosmos, that is, with all of nature. The morality presented by the philosopher does not annul the individuality of those who practice it, but it is adequate to welcome the other in his pain, in a movement of understanding and free interest for his fellow man, understanding that this relationship is more than necessary for the construction and improvement of the polis. Arthur Schopenhauer is a very up-to-date philosopher in his ethical doctrine, and can freely adapt to the present day, when society prioritizes anti-moral actions such as selfishness, the origin of social exclusion and irresponsibility towards the environment, the fruit of the profit culture, that is, capitalism. Compassion is, therefore, a bold proposal to deny one's own interests for the good of others, to live for the well-being of others. His philosophy even suggests that the individual will only be able to minimize his pain with asceticism, which means, with the denial of the will, that is, the thing in itself addressed by Kant, to whom he pays veneration. The will and its manifestations are the cause of perennial human dissatisfaction; the will is intrinsic and its satisfaction will lead the individual into an endless spiral: desire, satisfaction (boredom); desire..., thus, suffering. Schopenhauer is also known as the philosopher of representation; with this, he exposes a peculiar way of interpreting the world, which as such is nothing but the most absolute illusion; as well as the relentless efforts of human beings to achieve the dream of happiness. Finally, the ethics of compassion is an encounter of the human being with himself in the other, in responsibility and welcoming.